Rum där män möts : Samkönat begär i Knut Hamsuns "Hemmelig ve" - Johnsson, Henrik (Nordlit, 2020)
The article analyses Knut Hamsun’s short story ”Hemmelig ve” [”Secret Suffering”] (1897) from the perspective of queer theory. The article argues that Hamsun’s short story depicts same-sex desire between the narrator and a man described only as ”the stranger”. The stranger is interpreted as the narrator’s double, and as such a representation of the narrator’s forbidden desire. This interpretation is founded on a comparison between the 1897 version of the text, and an earlier version published as ”Underlige Sjæle” [”Strange Souls”] (1891), and on a close reading of the two men’s meetings. The article concludes with a discussion of Hamsun scholarship’s engagement with queer theory.